Digital twin technology : fundamentals and applications - Vohra, Manisha, 1994- (Hoboken, NJ : Wiley ; Beverly, MA : Scrivener Publishing, 2023)
DIGITAL TWIN TECHNOLOGY The book lucidly explains the fundamentals of digital twin technology along with its applications and various industrial real-world examples. Digital twin basically means a replicated model of any object or product in digital form. A digital twin has many advantages as it remains connected with the original object or product it is replicating and receives real-time data. Therefore, the obstacles and issues that could be encountered in a product or object can be known before their actual happening which helps to prevent errors and major losses which otherwise might have been incurred. The various capabilities of digital twin technology make it a powerful tool that can be used to effectively boost various sectors of the healthcare, automotive, and construction industries, among others. Although this technology has been making its way into various sectors, it has not yet received the kind of exposure necessary to increase awareness of its potential in these industries. Therefore, it is critical that a better understanding of digital twin technology is acquired to facilitate growth and to have it implemented in the various sectors so that transformation can be ushered in. Therefore, this book was designed to be a useful resource for those who want to become well acquainted with digital twin technology. Audience Engineers, researchers, and advanced students in information technology, computer science, and electronics, as well as IT specialists and professionals in various industries such as healthcare, automotive, and transportation.
Front Matter -- Overview of Digital Twin / Manisha Vohra -- Introduction, History, and Concept of Digital Twin / N Rajamurugu, M K Karthik -- An Insight to Digital Twin / Anant Kumar Patel, Ashish Patel, Kanchan Mona Patel -- Digital Twin Solution Architecture / Suhas D Joshi -- Role of Digital Twin Technology in Medical Sector-Toward Ensuring Safe Healthcare / SN Kumar, A Lenin Fred, LR Jonisha Miriam, Jane I Christina, H Ajay Kumar, Parasuraman Padmanabhan, Balazs Gulyas -- Digital Twin as a Revamping Tool for Construction Industry / A S Greeshma, Philbin M Philip -- Digital Twin Applications and Challenges in Healthcare / S Pavithra, D Pavithra, R Vanithamani, Judith Justin -- Monitoring Structural Health Using Digital Twin / Samaya Pillai, Venkatesh Iyengar, Pankaj Pathak -- Role and Advantages of Digital Twin in Oil and Gas Industry / J Prakash -- Digital Twin in Smart Cities / Manisha Vohra -- Digital Twin in Pharmaceutical Industry / Anant Kumar Patel, Ashish Patel, Kanchan Mona Patel -- Different Applications and Importance of Digital Twin / R Suganya, Seyed M Buhari, S Rajaram -- Digital Twin in Development of Products / Pedro Pablo Chambi Condori -- Possibilities with Digital Twin / Vismay Shah, Anilkumar Suthar -- Digital Twin / J Prakash -- Index
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed December 5, 2022).
John Wiley and Sons
Keywords: Digital twins (Computer simulation); Digital twins (Computer simulation)